Fabrication and characterization of Prussian blue screen-printed working electrode and their application for free chlorine monitoring in swimming pool water. (20th August 2021) - Kongkaew, Supatinee; Joonyong, Kavinna; Kanatharana, Proespichaya; Thavarungkul, Panote; Limbut, Warakorn
Highlights: A screen-printed Prussian blue electrode was fabricated on a flexible substrate. The proposed electrode accurately and precisely measured free chlorine. The proposed electrode fabrication provided good reproducibility. The proposed sensor was simple, cost-effective, and rapid. The proposed sensor can be applied to monitor swimming pool water quality. Abstract: A Prussian blue screen-printed working electrode (PB-SPWE) was fabricated for continuous detection of free chlorine compound (free-Cl) in water samples from swimming pools. Carbon and Prussian blue were deposited on a flexible substrate using a screen-printing technique. Different screen-printed PB-SPWEs demonstrated the good reproducibility of the electrode fabrication and were further incorporated with a lab-made flow cell in a flow injection (FI) analysis system. The electrochemical response via Prussian blue reaction was recorded at a potential of 50 mV vs. Ag/AgCl. High-throughput analysis was achieved by continuous injection of a standard NaOCl solution, and 336 measurements could be completed in 5.6 h. Under optimal conditions, the PB-SPWE was applied to determine free-Cl in several swimming pool water samples without any sample preparation. The results not only were in good agreement with the standard DPD (N, N‑diethyl-p-phenylenediamine) spectrophotometric method, but also presented excellent accuracy (recovery = 80.0 ± 0.2 to 109±1%) and precision (test by Wilcoxon Signed-Ranks) in measuring free-Cl concentrations. In summary, these results supported that the combination of PB-SPWE and FI-AMP can be applied to monitor swimming pool water quality, which can minimize the risk to swimmers' health. Graphical abstract: Image, graphical abstract